The International Conference on Health Informatics ICHI 2013, Vilamoura, Portugal on 7-9 November, 2013 - Zhang, Yuan-Ting (IFMBE Proceedings,, 2014)
This volume presents the proceedings of the International Conference on Health Informatics (ICHI). The conference was a new special topic conference initiative by the International Federation of Medical and Biological Engineering (IFMBE), held in Vilamoura, Portugal on 7-9 November, 2013. The main theme of the ICHI2013 was "Integrating Information and Communication Technologies with Biomedicine for Global Health". The proceedings offer a unique forum to examine enabling technologies of sensors, devices and systems that optimize the acquisition, transmission, processing, storage, retrieval of biomedical and health information as well as to report novel clinical applications of health information systems and the deployment of m-Health, e-Health, u-Health, p-Health and Telemedicine.